LITERATURE REVIEW: FAKTOR - FAKTOR YANG MEMPENGARUHI KEBERADAAN MIKROPLASTIK DI UDARA - Agripina, Ni Putu Angieta; Suryadhi, Made Ayu Hitapretiwi (ARCHIVE OF COMMUNITY HEALTH, 2025)
The excessive use of plastics leads to the presence of microplastics that are harmful to human health. The discovery of microplastics in human lung tissue has been widely revealed through and even microplastics can be a toxins. The purpose of this study is to determine the factors that influence the presence of microplastics in the air, especially in coastal areas in urban areas. Leading databases were searched through Google Scholar from 2016 - 2022. From 12,068 articles, 13 related articles were found and included in the review. Some of the factors that influence the presence of microplastics in the air are meteorological factors, climatic factors, anthropological factors, microplastic particles and space in the air. The most consistent characteristics of microplastics in the air in the form of fibres with long small sizes and red and blue colours. Prevention can be done by monitoring the presence of microplastics in the environment both water, soil and air, especially to limit human exposure. Key words : Microplastics, Air Pollution, Human Factors and Breathing